Physiochemical Characterization and Dematerialization of Coal Class F Flyash Residues from Thermal Power Plant - Mohammad Nadeem Akhtar; Janisaar Akhtar; Nazia Tarannum (Salehan Institute of Higher Education, 2019)
Class F flyash has a low percentage content of lime and is considered as a leading category of flyash generated in India with an average utilization of nearly 55% of flyash produced by the coal-burning power plant. The coal Class F flyash residue sample has been collected from Harduaganj, Thermal Power Station India. The paper illustrates the outcome of the study carried out to examine all the relevant features of the chemical and physical properties of Class F flyash sample. Elementary quantitative results from point analysis, SEM/EDS, FTIR, and pH analysis have been done in the chemical analysis of the study. The physical characterization of the sample is done by several experimental approaches to compare all the relevant features of Class F flyash sample and common soil. The main objective of this study is to evaluate whether the locally available Class F flyash from Harduaganj Thermal Power Station India, will provide satisfactory performance in fully or partially replacement of common soil. The performance evaluation of flyash and soil in different test results included bulk density, specific gravity, plasticity, maximum dry density, optimum moisture content, and permeability in accordance with the relevant IS or ASTM standards. Finally, the reported research recommended the selection of Class F flyash sample with low-lime content that provided the close correlation of its physical properties to the common soil.